Whereabouts [large type] - Lahiri, Jhumpa (Random House Large Print, 2021)
An English translation of a first Italian-language novel by the Pulitzer Prize-winning author of "The Lowland" follows the routines of a misfit city dweller who experiences a year of remarkable transformation in the aftermath of a parent's death.